2024
DOI: 10.1001/jama.2024.4459
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Mortality by Sexual Orientation in a Large, Prospective Cohort of Female Nurses

Sarah McKetta,
Tabor Hoatson,
Landon D. Hughes
et al.

Abstract: ImportanceExtensive evidence documents health disparities for lesbian, gay, and bisexual (LGB) women, including worse physical, mental, and behavioral health than heterosexual women. These factors have been linked to premature mortality, yet few studies have investigated premature mortality disparities among LGB women and whether they differ by lesbian or bisexual identity.ObjectiveTo examine differences in mortality by sexual orientation.Design, Setting, and ParticipantsThis prospective cohort study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…A recent prospective study found that lesbian and bisexual women died 20% and 37% earlier, respectively, than heterosexual women. 4 Individuals with intersectional identities (e.g., Black individuals who are gay/lesbian/bisexual or transgender) 5 may experience a heightened fear because of multiple minority stressors (e.g., heterosexism, racism, and classism) 6 as well as unique intersectional stigma and discrimination. 7 Discrimination negatively affects care for LGBTQþ individuals across the cancer continuum from prevention and early detection to diagnosis, treatment, and survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective study found that lesbian and bisexual women died 20% and 37% earlier, respectively, than heterosexual women. 4 Individuals with intersectional identities (e.g., Black individuals who are gay/lesbian/bisexual or transgender) 5 may experience a heightened fear because of multiple minority stressors (e.g., heterosexism, racism, and classism) 6 as well as unique intersectional stigma and discrimination. 7 Discrimination negatively affects care for LGBTQþ individuals across the cancer continuum from prevention and early detection to diagnosis, treatment, and survivorship.…”
Section: Introductionmentioning
confidence: 99%